Legal Responsibility by the Government Regarding Liquid Medicines that Cause Kidney Failure - Andhika Ihza Hanggara; Arief Budiono; H Hartanto; Yoesoef Moesthafa; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2023)
Ensuring public health is the duty of all human beings in the country. Providing legal certainty and protection is the government's duty, including providing safe and comfortable health services. The case of syrup drugs that cause kidney failure in children presents the latest challenge for the government regarding its failure to supervise operating permits and distribution permits for drugs in Indonesia. This turned out to result in several children dying after several times consuming syrup drugs containing ingredients that can trigger kidney failure. The state should be able to protect the public through the Consumer Protection Law, and the victims are children, so the Child Protection Law is then targeted. Even though as we know, that this country has a state institution that focuses on taking care of this, namely the Food and Drug Supervisory Agency (BPOM). So through this study, researchers will convey the analysis of accountability from BPOM and the role of UUPK in this problem. This research uses Juridical‐Normative research methods by testing the Law.